Synthesis and characterization of poly-L-lysine grafted SBA-15 using NCA polymerization and click chemistry - Kar, Mrityunjoy; Malvi, Bharmana; Das, Anindita; Panneri, Suyana; Sen Gupta, Sayam (Journal of Materials Chemistry, 2011)
Poly-L-lysine (PLL) grafted ordered mesoporous material was prepared by a combination of NCA polymerization and click chemistry. Large pore SBA-15 with a mesopore diameter of similar to 12 nm was synthesized using a previously reported method. The surface of this SBA-15 material was modified with azidopropyl groups. This ``clickable'' SBA-15 was then reacted with an alkyne terminated poly-L-lysine synthesized by the ring-opening polymerization of 3-cbz-L-lysine NCA with N-TMS propargylamine as the initiator. This procedure allows grafting of a uniform polymer film with a high polymer loading. No appreciable pore blocking was observed upon grafting of PLL. No change in the periodic structure of the SBA-15 was observed throughout the grafting process. The SBA-15 PLL conjugate was characterized using (13)C and (29)Si NMR, XRD, FT-IR, N(2) adsorption-desorption and thermogravimetry. The results indicate that polypeptides can be easily grafted onto various ordered mesoporous materials by this ``grafting to'' methodology with accessible pores and high loadings of the polypeptide.